1990
DOI: 10.1002/art.1780331007
|View full text |Cite
|
Sign up to set email alerts
|

Use of molecular cloning methods to map the distribution of epitopes on topoisomerase I (Scl‐70) recognized by sera of scleroderma patients

Abstract: We report the initial molecular characterization of the autoimmune response against DNA topoisomerase I ( t o p I; Scl-70). Sera from 36 patients with scleroderma and 4 healthy control subjects were studied using 6 subcloned portions of topo I. Twenty-three sera recognized at least 2 independent epitopes on the molecule. Therefore, anti-topo I, like other non-organ-specific autoantibodies characterized to date, is polyclonal and multifocal. The cloned protein should prove suitable for sensitive early detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…The location of ER3 was consistent with that of major B cell epitope determined by previous studies (45,46). In this study, we showed that each of four different B cell epitopes was associated with the different HLA-DR genes, suggesting that the specific immune response to each B cell epitope is controlled by different T cell epitopes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The location of ER3 was consistent with that of major B cell epitope determined by previous studies (45,46). In this study, we showed that each of four different B cell epitopes was associated with the different HLA-DR genes, suggesting that the specific immune response to each B cell epitope is controlled by different T cell epitopes.…”
Section: Discussionsupporting
confidence: 90%
“…Autoantigenic B cell epitopes on topo I molecule were analyzed by several investigator groups (34,(44)(45)(46)(47). The location of ER3 was consistent with that of major B cell epitope determined by previous studies (45,46).…”
Section: Discussionsupporting
confidence: 68%
“…47 Scl-70 antibodies bind to the active site of topoisomerase I and inhibit topoisomerase I activity, preventing DNA relaxation. [48][49][50][51] It remains unclear if scl-70 antibodies are pathologic or an epiphenomena. 52 However, antibodies to topoisomerase I (Scl-70) are specific for scleroderma and are associated with a higher risk of diffuse skin disease, pulmonary involvement, and a worse prognosis.…”
Section: Radiation Sensitivity Of Sclerodermamentioning
confidence: 99%
“…In contrast to the finding of a single epitope on Topo I, Verheijen et al (13) showed the reactivity of anti-Topo I sera against three different epitope regions toward the C-terminal of Topo I. D'Arpa et al (14) expressed six portions of Topo I and demonstrated that most of anti-Topo I-positive sera recognize multiple epitopes. Kuwana et al (17) detected four epitope regions on Topo I from the N-terminal to C-terminal.…”
Section: Discussionmentioning
confidence: 96%
“…The full-length cDNA sequence of Topo I was subsequently cloned (11). The availability of Topo I cDNA has stimulated a number of investigators to fine-map Ab epitopes on the Topo I molecule (12)(13)(14)(15)(16)(17). Using Western blot with recombinant Topo I fragments as Ags, several anti-Topo I Ab epitopes distributed from the N-terminal to the C-terminal portion of Topo I molecule have been reported (12,17,18).…”
mentioning
confidence: 99%